Load cells help in search for world-class rowers
Applied Weighing is set to make a huge impact on the future of the sport of rowing after developing a pioneering rowing machine that measures strength in three key areas of an athlete's body. The first of its kind in the UK, this novel rowing machine is a collaboration between Imperial College in London, Peter Haining, a previous GB medal winner and coach to the GB rowing team, and Julian Glasspole of Applied Weighing. The objective was to develop a rowing machine that could not only help optimise the performance of experienced athletes, but also help to identify new talent. Research proves that rowers spread their strength over three parts of their body; the back, the arms and the legs. Top class rowers can spread their strength evenly between these three points, thus optimising their performance. Novice rowers, however, will find it difficult to achieve an equal balance of weight between the three key areas. To counteract this problem Applied Weighing designed three load cells that are positioned under the seat, on the handlebars and on the foot rests. An electrical current from each point is transferred into a wattage output, which is connected to a PC and downloaded as comprehensive data. Bespoke software has been developed which allows the user to study the data alongside previous records, and also analyse the statistics from the three key areas. Peter Haining believes that this technology will have a big impact on the future of athlete training programmes. He comments, "We knew that the way to improve rowers performance would be to balance their weight between the three key areas, but were unsure how we could obtain the data. Engineers at Applied Weighing assessed our needs and were able to design complex weighing gauges that could record the required data". Haining's aim is to equip every high performance-rowing club in the UK with the new technology. "Great Britain already has some of the best rowers in the world but with this new technology we can pinpoint the next Steve Redgrave or Matthew Pinsent even before they've hit the water". Prof Alison McGregor, head of the Biodynamic laboratory at the Imperial College became involved in the project after her research into back injuries in rowers. She says, "This equipment gives us exactly the information we need to prove our theory on back strain in athletes. Our research is now based on evidence, rather than theory". Julian Glasspole, MD of Applied Weighing became involved with the project after training with his local rowing club. He says, "I knew that I was rowing inefficiently but was unable to locate the problem. I discussed this with the design engineers at Applied who informed me that they were capable of manufacturing minute weight gauges. We are delighted to have been able to provide such a valuable solution".